(untitled) (Research, Society and Development, 2021)
The far west region of Santa Catarina (FWSC) state in southern Brazil was indicated as a microcenter of diversity of the Zea genus. In this region, local popcorn varieties are grown in small areas, but in a significant number of farms. The present study aimed to characterize the diversity of 41 local populations from that region, based on phenology and morphological characters of plant, ear and grain. Therefore, an experimental design of complete randomized blocks with two replications was conducted. The data allowed to identify a rich diversity of popcorn in the FWSC for the characteristics of plant, ear, and grain, as well as for the phenology. For the color, 20 populations presented white grain, nine black, nine yellow, two red and one orange. Regarding the cycle, all varieties of yellow and round grains were considered hyper early/early and the varieties of white grains, intermediate/late. Average plant height varied from 1.8 to 3.2 m, while the weight of one thousand kernels varied from 80.9 to 200.4 g. The accumulated day degrees for tasseling ranged from 689.05 to 1,090.57. Based on the cluster analysis of qualitative and quantitative characters, three groups were formed, and five populations were isolated. The inclusion of plant characteristics and phenology can be an important and complementary tool for studies in popcorn races. Trends in some plant characteristics were observed within popcorn varieties with the same grain features. This result is important information for popcorn genetic breeding strategies.